2003
DOI: 10.1002/jnr.10584
|View full text |Cite
|
Sign up to set email alerts
|

NFAT4 is expressed in primary astrocytes and activated by glutamate

Abstract: Calcium signaling is a critical component of astrocyte activation but little information is available regarding the identity and function of transcriptional targets of calcium signaling in these cells. As a first step in elucidating the mechanisms that astrocytes use to regulate transcription in response to raised intracellular calcium concentrations, we have investigated expression and activation of the calcium activated transcription factors of the NFAT family. We report here that NFAT4 is expressed in U373 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…These events were blocked by CsA and EGTA, and overexpression of NFAT1 enhanced ionomycin-stimulated BACE1 promoter activity. NFAT1 has been found in the brain and in neuronal cells (Plyte et al, 2001), and NFAT4 is expressed and activated in astrocytes in the presence of elevated intracellular calcium (Jones et al, 2003). Interestingly, although we found both NFAT1 and NFAT4 in SH-SY5Y cells and primary cortical cultures, only NFAT1 was activated by disruption of intracecullar calcium levels.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…These events were blocked by CsA and EGTA, and overexpression of NFAT1 enhanced ionomycin-stimulated BACE1 promoter activity. NFAT1 has been found in the brain and in neuronal cells (Plyte et al, 2001), and NFAT4 is expressed and activated in astrocytes in the presence of elevated intracellular calcium (Jones et al, 2003). Interestingly, although we found both NFAT1 and NFAT4 in SH-SY5Y cells and primary cortical cultures, only NFAT1 was activated by disruption of intracecullar calcium levels.…”
Section: Discussionmentioning
confidence: 47%
“…Although NFAT was first identified in T cells, recent studies have demonstrated NFAT protein expression in other immune-related cells, as well as in many other tissues, including the spleen, thymus, lymph node, and brain (Ochi et al ., 1994;Masuda et al ., 1995;Plyte et al ., 2001;Eberl & Littman, 2003). In the brain, NFAT1 is normally detected in neuronal cells (Plyte et al ., 2001), and NFAT4 is also expressed and activated in astrocytes in the presence of elevated intracellular calcium (Jones et al ., 2003), inducing target gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…However, both Cn (65) and NFAT4 (66) expression has been described in astrocytes. NFAT4 is activated by glutamate-mediated Ca 2ϩ increase (66), and Cn signaling mediated survival of reactive astrocytes (65). In neurons, Tat activates PI3K (67), increases levels of inositol 1,4,5-triphosphate, releases calcium from inositol 1,4,5-triphosphate-sensitive endoplasmic reticulum internal stores, and increases activity of the protein kinase C isoforms ␣, -, and (68).…”
Section: Discussionmentioning
confidence: 99%
“…5D). Furthermore, expression of ⌬CnA blocked the increase in the levels of NFBp65 and NFAT4 (an isoform found in astrocytes) (Jones et al, 2003) elicited by 16 h of exposure to LPS or 3 h after TNF-␣ (data not shown) in mock-transfected astrocytes (Fig. 5E) (supplemental Fig.…”
Section: Calcineurin Inhibits a Canonical Proinflammatory Pathway In mentioning
confidence: 90%